Caracterização mecânica do compósito produzido da tala do Buriti - Silva, André Henrique Brandão da (Universidade Federal Rural do Semi-Árido, 2019)
The society has always sought combinations with the purpose of producing a new material, with the result that the composite sandwiches were created. These materials are capable of uniting the positive characteristics of each of its components in its products, thus having the best qualities of each. The objective of this work was to mechanically fabricate and characterize composites obtained from the buriti splice fiber, thus proposing an alternative of core material in composite sandwiches. Two types of materials were developed, all using R190 crystal polyester resin and using the Hand Lay Up (HL) production process, with one using glass fiber, resin and buriti, the other using resin and buriti. Water density and expansion properties were also analyzed. For this, the standards ASTM D3039, for tensile test, ASTM D790 for flexural test and ABNT NBR 7190 were used. The tensile tensions found for the buriti sandwich composites were the ones that presented the best results, being superior to those of fiber and resin. In the flexural tests the ones that had better results were those with only fiber and resin, those that contained buriti presented crushing and buckling before the rupture, finally the found densities were of 62,57 kg / m3 being below the average of the market having also low contraction and expansion of their fibers. In this way the natural buriti fiber is excellent for traction applications and when low weight is desired
Monografia
Keywords: Tala de Buriti; Compósito sanduiche; Hand Lay Up; Caracterização mecânica; Densidade; Composite sandwich; Characterize mechanically; Density; ENGENHARIAS::ENGENHARIA MECANICA